Revitalisasi Pengelolaan Pasar Titi Kuning Medan Oleh PD Pasar Kota Medan - Ismi Andari; Tengku Maya Magdina (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2020)
Revitalization of traditional markets should be done by arranging and improving traditional markets, where weaknesses in traditional markets that cause a decline in the competitiveness of traditional markets themselves must be immediately addressed. In this study the theory used is public policy theory, this is because revitalization is one of public policy. This type of research used by researchers in this study is a qualitative approach with a descriptive study. This research was conducted at the Medan City Market Regional Company as the only company that was given the authority by the Medan City Government to manage all markets in the city of Medan. The results of this study explain that the traditional market revitalization model based on social capital, from the results of the field data in the Titi Kuning traditional market shows that revitalization with an emphasis on the physical dimension of the market by ignoring other dimensions, especially social capital actually makes the traditional market experience a slump and is not successful Revitalization activities must embrace or use other dimensions especially social capital such as social networks, trust and compliance with existing rules or norms so that revitalization can develop and advance.